Karakteristik Penderita Kanker Serviks dalam Mencari Informasi Kesehatan Tambahan - Sonia Isnabila; Lestari Sudaryanti; Brahmana Askandar Tjokroprawiro (Universitas Batanghari Jambi, 2023)
Cervical cancer is the most common malignancy affecting women in developing countries, including Indonesia. In Indonesia, the incidence of cervical cancer is the type of cancer with the highest incidence rate after breast cancer in women. Women who are diagnosed with cancer not only experience the physical burden of illness and treatment, but also have psychological and social needs, including feelings of anxiety, anxiety, uncertainty, and so on. Even though they suffer from a dangerous disease they never give up hope to continue to survive. Moreover, they are more motivated to seek additional health information. This study aims to find out the characteristics of cervical cancer sufferers in seeking additional health information. This study uses a descriptive quantitative method with a purposive sampling technique. Based on this study, most of the cervical cancer patients who came to RSUD Dr. Soetomo were 50-59 years old, with a moderate level of education, and a housewife. Based on the characteristics when seeking additional health information, most of them seek additional information by using oral media. Those who use internet media mostly visit media that has low credibility. After getting the information they needed they felt relieved.